Post‐synthetic Rhodium (III) Complexes in Covalent Organic Frameworks for Photothermal Heterogeneous C−H Activation - Li, Teng; Zhang, Pei‐Lin; Dong, Long‐Zhang; Lan, Ya‐Qian (Angewandte Chemie International Edition, 2024)
Although photocatalytic C−H activation has been realized by using heterogeneous catalysts, most of them require high‐temperature conditions to provide the energy required for C−H bond breakage. The catalysts with photothermal conversion properties can catalyze this reaction efficiently at room temperature, but so far, these catalysts have been rarely developed. Here, we construct bifunctional catalysts Rh‐COF‐316 and ‐318 to combine photosensitive covalent organic frameworks (COFs) and transition‐metal catalytic moiety using a post‐synthetic approach. The Rh‐COF enable the heterogeneous C−H activation reaction by photothermal conversion for the first time, and exhibit excellent yields (up to 98 %) and broad scope of substrates in [4+2] annulation at room temperature, while maintaining the high stability and recyclability. Significantly, this work is the highest yield reported so far in porous materials catalyzing C(sp2)−C(sp2) formation at room temperature. The excellent performances can be attributed to the COF‐316, which enhances the photothermal effect (ΔT=50.9 °C), thus accelerating C−H bond activation and the exchange of catalyst with substrates. In this work, a general post‐synthetic strategy for constructing bifunctional catalysts, Rh‐COF, which connect photosensitive covalent organic frameworks and transition‐metal catalytic groups through covalent bonding, was developed. Fascinatingly, such complexes enable efficient photothermal conversion properties, which can improve the photothermal catalytic performances in C−H activation to obtain excellent yield, substrate suitability and recyclability.